How plume‐ridge interaction shapes the crustal thickness pattern of the Réunion hotspot track. (9th August 2017) - Bredow, Eva; Steinberger, Bernhard; Gassmöller, Rene; Dannberg, Juliane
Abstract: The Réunion mantle plume has shaped a large area of the Earth's surface over the past 65 million years: from the Deccan Traps in India along the hotspot track comprising the island chains of the Laccadives, Maldives, and Chagos Bank on the Indian plate and the Mascarene Plateau on the African plate up to the currently active volcanism at La Réunion Island. This study addresses the question how the Réunion plume, especially in interaction with the Central Indian Ridge, created the complex crustal thickness pattern of the hotspot track. For this purpose, the mantle convection code ASPECT was used to design three‐dimensional numerical models, which consider the specific location of the plume underneath moving plates and surrounded by large‐scale mantle flow. The results show the crustal thickness pattern produced by the plume, which altogether agrees well with topographic maps. Especially two features are consistently reproduced by the models: the distinctive gap in the hotspot track between the Maldives and Chagos is created by the combination of the ridge geometry and plume‐ridge interaction; and the Rodrigues Ridge, a narrow crustal structure which connects the hotspot track and the Central Indian Ridge, appears as the surface expression of a long‐distance sublithospheric flow channel. This study therefore provides further insight how small‐scale surface features are generated by the complex interplay between mantle and lithospheric processes. Key Points: Réunion plume model predicts crustal thickness pattern comparable to actual hotspot track Gap between Maldives and Chagos generated due to ridge geometry and plume‐ridge interaction Rodrigues Ridge formed by sublithospheric flow channel between plume and Central Indian Ridge